Changes in Outcome and Complication Rates of Very-low-birth-weight Infants in One Tertiary Center in Southern Taiwan Between 2003 and 2010 - Shen-Dar Chen; Yung-Chieh Lin; Chin-Li Lu; Solomon Chih-Cheng Chen (Pediatrics and Neonatology)
Neonatal intensive care has changed dramatically over the past few decades and the survival of infants has generally improved in many countries. The purpose of this study was to explore the recent evolution of mortality and morbidities among very-low-birth-weight (VLBW) infants in southern Taiwan. Methods: We retrospectively reviewed the medical records of VLBW (birth weight <1500 g) infants who were admitted to a neonatal intensive care unit at a tertiary medical center in southern Taiwan from 2003 to 2010. The study period was divided into two cohorts: the first cohort of 2003–2006 and the second cohort of 2007–2010. Demographic profiles and complications were recorded, including the following information: sex, birth body weight (BBW), gestational age (GA), Apgar score, patent ductus arteriosus (PDA), necrotizing enterocolitis, retinopathy, chronic lung disease (CLD), inguinal hernia, and sepsis. The length of stay (LOS) in hospital was compared between the two cohorts. Results: A total of 420 (212 male) VLBW infants were enrolled with 52 (12.4%) deaths. Compared to surviving infants, deceased infants had significantly lower GA, Apgar scores, and BBW. The mortality of VLBW infants remained static between the two birth cohorts, but the incidence of major morbidities generally decreased. The LOS for overall surviving infants and the proportion of LOS > 60 days were both reduced in the period of 2007–2010. With further stratification by BBW, the major reduction of long LOS was only found in the group of BBW ≥ 1000 g. The multivariate logistic regression model found PDA, CLD, and BBW < 1000 g were major complications to be associated with long LOS among surviving infants. Conclusion: Periodic evaluation of the mortality and morbidity of preterm infants can help to understand the changes and trends of our neonatal care. Further study using the national dataset to provide more representative information is warranted.